Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Negeri Sipil Menggunakan Metode (Combinative Distance – Based Assessment) Pada Kantor Camat Sei Kepayang - Munawir Akmal Siahaan (Bulletin of Information Technology (BIT), 2022)
Performance appraisal is carried out to evaluate the performance of existing employees and can also be used by agencies to spur employees to work better, so an agency can give awards to employees who are considered to be outstanding. Awards can be in the form of awards, appointments in positions, promotion, or others, which can give enthusiasm and motivation to employees. The system that runs in the Sei Kepayang sub-district office still has weaknesses, namely the employee appraisal process is still done manually and there is also no system for decision-making that supports employee performance appraisal. In solving these problems, the researcher uses the method (combinative distance-based assessment) which is useful for calculating employee performance appraisals, so that the method (combinative distance-based assessment) can find out which employees get the highest achievement score. while the program to create the system uses a visual basic program. This application will display performance appraisals automatically and the final report can be printed directly, by month and year. This study aims to produce applications that become supporting facilities as a tool for calculating employee performance more effectively